Procedimento de análise do impacto ambiental do ruído de tráfego em terminais de transporte coletivo urbano: um estudo de caso no município de Fortaleza - Silveira, Roger Cajazeiras (2008)
The process of urbanization of large cities and the increase of the number of motorized trips and the increment of the industrial activities has been worsening the environmental impacts, in particular the noise pollution. That pollution troubles the population, contributes to the degradation of life quality and is also a public health problem. The strategy of using integration terminals aims to facilitate the transportation of the population in those cities. However, there is a concentration of the bus operation on a relatively small space, what generates high noise levels. This research intends to diagnose the noise level inside the terminals inthe city of Fortaleza. The results will be compared with the existing legislation and the parameters that influence these levels will be studied.